Effect of Nitrogen Source and Inorganic Phosphate Concentration on Methanol Utilization and PEX Genes Expression in Pichia pastoris - A. M. Rumjantsev; O. V. Bondareva; M. V. Padkina; E. V. Sambuk (The Scientific World Journal)
Methylotrophic yeast Pichia pastoris has proved to be especially useful for production of various heterologous proteins. In biotechnology it is very important to maintain the balance between high levels of heterologous gene expression and cell viability. Decisive understanding of gene regulation mechanisms is essential for reaching this goal. In this study, we investigated the effect of different nitrogen sources and phosphate concentration in media on methanol utilization. It was shown that expression levels of main genes, which are involved in methanol utilization (MUT genes) and in functioning of peroxisomes (PEX genes), are maximal when ammonium sulphate is used as a nitrogen source. Expression of these genes is decreased in media with poor nitrogen sources, such as proline. Addition of rapamycin to the media completely removed repression of AOX1 promoter in media with proline, which allows proposing that Tor-kinase is involved in establishing of nitrogen regulation of this gene. It was also shown that MUT genes expression levels get higher, when the phosphate concentration in media is increased.